Peningkatan Hasil Belajar Matematika Melalui Metode Bermain Kantong - Samosir, Ajun (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This research was motivated by the low learning outcomes of grade II students at SD Negeri 6 Onanrunggu on the place value material. Based on preliminary observations, it is known that the mean value of class II students on the place value material is 47.65. One of the causes of low learning outcomes is the lack of planning in processing the material to be taught. This type of research the researcher uses is classroom action research (PTK). The subjects in this study were the second grade students of SD Negeri 6 Onanrunggu with a total of 22 students. Based on the results of this study, it shows that the second grade students of SD Negeri 6 Onanrunggu feel a change in understanding the value of the place of numbers and show that the method of playing the number bag can improve the learning outcomes of the second grade students of SD Negeri 6 Onanrunggu in the place value material with evidence of an increase in learning outcomes. Cycle I the percentage of completeness reached 36.37% with 8 students who completed. In the second cycle the percentage of completeness reached 77.2% with 17 students who completed. Cycle III the percentage of completeness reaches 90% with 20 students who complete. Keywords: play the pocket; the value of numbers  Abstrak: Penelitian ini di latar belakangi oleh rendahnya hasil belajar siswa kelas II di SD Negeri 6 Onanrunggu pada materi nilai tempat. Berdasarkan pengamatan awal diketahui nilai rata-rata siswa kelas II pada materi nilai tempat yaitu 47,65. Salah satu penyebab rendahnya hasil belajar yaitu kurangnya perencanaan dalam mengolah materi yang akan diajarkan. Jenis penelitian yang digunakan peneliti adalah penelitian Tindakan kelas (PTK). Subyek dalam penelitian ini yaitu siswa kelas II SD Negeri 6 Onanrunggu dengan jumlah 22 siswa. Berdasarkan hasil penelitian ini menunjukkan bahwa siswa kelas II SD Negeri 6 Onanrunggu merasakan perubahan dalam memahami nilai tempat bilangan dan menunjukkan bahwa metode bermain kantong bilangan dapat meningkatkan hasil belajar siswa kelas II SD Negeri 6 Onanrunggu dalam materi nilai tempat dengan dibuktikan adanya peningkatan hasil belajar. Siklus I presentase ketuntasan mencapai 36,37% dengan siswa yang tuntas terdapat 8 siswa. Siklus II presentase ketuntasan mencapai 77,2% dengan siswa yang tuntas sebanyak 17 siswa. Siklus III presentase ketuntasan mencapai 90% dengan siswa yang tuntas sebanyak 20 siswa. Kata Kunci: bermain kantong; nilai tempat bilangan